Double-layer spinning structure and spinning process of composite fiber

Through the double-layer spinning structure of the composite fiber, the combination of a deformation memory outer layer and a spinning inner layer is adopted to solve the problem of poor spinning stability, achieve the temperature response and performance consistency of the fiber, and is suitable for the textile and clothing fields.

CN120776492APending Publication Date: 2025-10-14DONGGUAN TINGYUXUAN GARMENT CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511059082.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-30
Publication Date
2025-10-14

AI Technical Summary

Technical Problem

In the existing spinning process, the rheological properties of the spinning solution are difficult to accurately control, resulting in uneven fiber thickness during the spinning process, affecting the strength and toughness of the fibers, and poor spinning stability, which affects the appearance quality and physical properties of the fabric.

Method used

It adopts a double-layer spinning structure of composite fibers, including a shape-memory outer layer formed by thermo-deformable polyurethane memory material and a spinning inner layer of cotton and polyester blended core. It is formed in one piece through coaxial electrospinning, combined with temperature response characteristics and microporous interlocking structure to ensure that the two layers are tightly combined.

Benefits of technology

It improves the spinning stability and performance consistency, enhances the air permeability, moisture absorption and durability of the fiber, adapts to changes in different temperature environments, extends the service life, and is suitable for the textile and clothing fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120776492A_ABST
    Figure CN120776492A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of fabric spinning, in particular to a double-layer spinning structure of composite fiber and a spinning technology.The double-layer spinning structure comprises a composite fiber body, the composite fiber body comprises a deformation memory outer layer and a spinning inner layer, the deformation memory outer layer is made of thermally-induced deformation polyurethane memory materials, and the spinning inner layer is made of thermally-induced deformation polyurethane memory materials. The spinning inner layer is a cotton and polyester blended core; the glass transition temperature Tg of the thermally induced deformation polyurethane memory material is 35 + / -2 DEG C; the cotton accounts for 50-70% of the spinning inner layer, and the polyester accounts for 30-50% of the spinning inner layer; the deformation memory outer layer and the spinning inner layer are integrally formed through coaxial electrostatic spinning. Through reasonable design and an advanced manufacturing process, the fabric has various excellent performances such as temperature response, comfort and durability, and has a wide application prospect in the fields of spinning, clothing and the like.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of fabric spinning, in particular to a double-layer spinning structure and spinning process of composite fibers. BACKGROUND

[0002] In the textile industry, fabric spinning technology is crucial, as it directly affects the quality and performance of the fabric. However, the current fabric spinning field faces the serious problem of poor spinning stability. In existing spinning processes, the rheological properties of the spinning solution are difficult to accurately control. The viscosity of the spinning solution is affected by factors such as temperature, humidity, and additive content. Small fluctuations in these factors can cause changes in the flowability of the spinning solution, resulting in uneven fiber thickness during the spinning process, with the presence of thick and thin fibers. In the stretching stage, unstable stretching multiples and stretching speeds can also cause uneven internal structure of the fibers, affecting the strength and toughness of the fibers.

[0003] Poor spinning stability has a series of adverse consequences. The appearance quality of the fabric is severely affected, with uneven surfaces and imperfections, reducing the aesthetic appeal and market competitiveness of the product. The physical properties of the fabric are also unstable, with large fluctuations in strength, elasticity, and other indicators, making it difficult to meet the needs of high-end application fields. Therefore, there is an urgent need to improve the existing fabric spinning technology to improve the stability of spinning and produce higher quality and better performing fabric products. SUMMARY

[0004] To solve the above problems, the present application adopts a reasonable design and advanced manufacturing process to provide a double-layer spinning structure and spinning process of composite fibers with temperature response, comfort, durability, and other excellent properties, which has a wide application prospect in the fields of textiles, clothing, and others.

[0005] The technical scheme adopted by the present application is as follows: a double-layer spinning structure of composite fibers, comprising a composite fiber body, the composite fiber body comprising a shape memory outer layer and a spinning inner layer, the shape memory outer layer being formed of a thermal-induced shape memory polyurethane material, and the spinning inner layer being a cotton and polyester blended core; the glass transition temperature Tg of the thermal-induced shape memory polyurethane material is 35±2℃; the cotton accounts for 50-70% and the polyester accounts for 30-50% in the spinning inner layer; the shape memory outer layer and the spinning inner layer are integrally formed by coaxial electrospinning.

[0006] Further improvement of the above scheme is that the thermal-induced shape memory polyurethane material comprises the following components: Shape memory polyurethane: 80-90wt%; Nano-silicon dioxide: 5-8wt%; Anti-ultraviolet agent: 2-5wt%.

[0007] A further improvement of the above scheme is that the particle size of the nano-silicon dioxide is 20-40 nm; the anti-ultraviolet agent is a benzotriazole.

[0008] A further improvement of the above scheme is that the fiber fineness of the inner layer of the spun yarn is 1.2-1.8D, and the twist is 300-400 TPM.

[0009] A further improvement of the above scheme is that the cross-sectional shape of the composite fiber body is an eccentric circular ring structure, and the outer layer thickness ratio of the shape memory outer layer is 30±5%; the diameter of the inner layer of the spun yarn is 10-25 μm.

[0010] A further improvement of the above scheme is that the outer surface of the inner layer of the spun yarn is provided with a pit, and the pit is filled by coaxial electrospinning to form a microporous interlocking structure, the depth size of the pit is 2-5 μm, and the diameter is 1-3 μm.

[0011] A further improvement of the above scheme is that the outer surface of the shape memory outer layer is provided with a spiral groove, the groove depth size of the spiral groove is 0.5-1.2 μm, and the pitch is 15-30 μm; the surface area ratio of the spiral groove is ≥40.

[0012] A further improvement of the above scheme is that the preparation process of the composite fiber body comprises: The polyurethane solution electrospinning nozzle is spun, and the electrospinning nozzle is a coaxial double-channel structure: the electrospinning nozzle comprises an inner channel and an outer channel, the inner channel is used for hot melt spinning of the cotton and polyester blended core, and the inner channel is extruded to form an inner layer of spun yarn after cooling at a temperature of 60-80 ℃; the outer channel is used for electrospinning of a polyurethane solution with a concentration of 18-22 wt%, and the voltage is 25-35 kV; the polyurethane solution electrospinning nozzle is spun to coat the inner layer of the spun yarn to form a shape memory outer layer.

[0013] A further improvement of the above scheme is that the composite fiber body has temperature-responsive deformation characteristics: when the temperature is >Tg, the outer layer shrinkage is ≥15%; when the temperature is <Tg, the deformation recovery rate is ≥98%.

[0014] A further improvement of the above scheme is that the composite fiber body is used for temperature-regulating fabric, and the weaving density of the composite fiber body is 80-120 roots / cm²; when the environmental temperature is >35 ℃, the composite fiber body changes the weaving density of the composite fiber body under the action of the shape memory outer layer.

[0015] A spinning process for preparing a double-layer spun yarn structure of the composite fiber comprises the following steps: Step S1, core pretreatment: cotton and polyester are mixed in a ratio of 50-70%:30-50%, and a fiber fineness of 1.2-1.8D and a twist of 300-400TPM are formed by melt spinning to form a spinning inner layer; Step S2, polyurethane solution preparation: shape memory polyurethane 80-90wt%, nano silicon dioxide 5-8wt%, benzotriazole ultraviolet resistant agent 2-5wt% are dissolved in DMF solvent, and a spinning solution with a concentration of 18-22wt% is prepared; Step S3, coaxial electrospinning: the core layer is extruded through the inner channel, and the cooling roller temperature is 60-80℃; the polyurethane solution is extruded through the outer channel, and the core layer is coated by applying a static voltage of 25-35kV; Step S4, microporous interlocking forming: control the polyurethane solution to fill the surface pits of the core layer to form a microporous interlocking structure.

[0016] Further improvement of the above scheme is that in step S2, the spinning solution is aged: aging temperature: 40±2℃; aging time: 12-24h; viscosity after aging: 4500±500mPa·s.

[0017] Further improvement of the above scheme is that it further includes spiral groove forming: when the fiber is not completely cured, spiral grooves are formed by impressing a textured roller when the curing degree is 60-70%.

[0018] The present application has the following advantages: Compared with existing spinning structures, the deformation memory outer layer of the present application is formed by a thermally induced deformation polyurethane memory material with a glass transition temperature Tg=35±2℃, so that the composite fiber has unique temperature response capability. When the ambient temperature reaches or approaches the glass transition temperature, the deformation memory outer layer can undergo reversible deformation. In daily life, when the body temperature of the human body rises or the external environment temperature rises to the interval of 33~37℃, the deformation memory outer layer will deform, thereby changing the structure of the composite fiber, which may increase the gap between the fibers, improve the air permeability, and make people feel more cool and comfortable; when the temperature decreases, it can restore to the initial state, ensuring the stability of the fiber. The spinning inner layer adopts a cotton and polyester blended core, with cotton accounting for 50~70% and polyester accounting for 30~50%. Cotton fiber has good moisture absorption and softness, can absorb sweat excreted by the human body, keep the skin dry, and give people a comfortable touch; polyester has high strength, wear resistance, wrinkle resistance and other advantages, the combination of the two makes the spinning inner layer have moisture absorption, comfort and durability. It not only ensures the practicality of the composite fiber in daily use, but also improves its service life and reduces damage caused by friction, washing and other factors. The deformation memory outer layer and the spinning inner layer are integrally formed by coaxial electrospinning. The process ensures the close combination of the two-layer structure, making the overall performance of the composite fiber more stable. Integrally formed avoids the problem of separation or stratification between the two layers, ensuring the reliability of the composite fiber in the long-term use process. At the same time, coaxial electrospinning can accurately control the thickness and distribution of the two layers, making the performance of the composite fiber more uniform and consistent, which is conducive to large-scale production and application. The present application combines the advantages of various materials, through reasonable design and advanced manufacturing process, has temperature response, comfort and durability and other excellent properties, and has broad application prospects in the fields of textiles, clothing and other fields.

[0019] The spinning process for preparing the double-layer spinning structure of the composite fiber mixes cotton and polyester in a specific ratio in the blended core pretreatment step, and forms a spinning inner layer with a specific fiber fineness and twist through melt spinning. The reasonable ratio of cotton and polyester not only plays the hygroscopicity and soft touch of cotton, but also combines the high strength and wear resistance of polyester, so that the spinning inner layer has good comprehensive performance. Suitable fiber fineness and twist can ensure the uniformity and stability of the spinning inner layer, lay a foundation for the overall performance of the subsequent composite fiber, and avoid structural defects caused by uneven fiber thickness or improper twist. In the polyurethane solution preparation step, shape memory polyurethane, nano silicon dioxide and benzotriazole ultraviolet resistant agent are dissolved in DMF solvent in a certain proportion to prepare the spinning solution. The shape memory polyurethane gives the composite fiber the function of thermal deformation memory, and the glass transition temperature can make the fiber reversibly deform according to the change of environmental temperature. The addition of nano silicon dioxide enhances the strength and wear resistance of the fiber, and improves the service life of the composite fiber. The benzotriazole ultraviolet resistant agent can effectively absorb ultraviolet rays, protect the fiber from ultraviolet damage, and prolong the use time of the fiber in outdoor environment. The coaxial electrospinning step extrudes the core layer through the inner channel and shapes it through the cooling roller, and extrudes the polyurethane solution through the outer channel and applies an electrostatic voltage to coat the core layer. It ensures that the two-layer structure is tightly combined, the temperature control of the cooling roller ensures the forming quality of the spinning core layer, and the application of the electrostatic voltage makes the polyurethane solution uniformly coat the core layer, forming a complete and stable double-layer structure. The microporous interlocking forming step controls the polyurethane solution to fill the surface pits of the core layer, forming a microporous interlocking structure. It enhances the bonding force between the two layers, makes the overall performance of the composite fiber more stable, and improves the mechanical properties and stability of the composite fiber. At the same time, the microporous structure may give the composite fiber some special properties, such as air permeability and adsorbability. Through the synergistic effect of each step, the composite fiber double-layer spinning structure prepared by the present application has excellent comprehensive performance, good practicality and application prospect. BRIEF DESCRIPTION OF DRAWINGS

[0020] Figure 1 Figure 1 is a structural schematic diagram of the double-layer spinning structure of the composite fiber of the present application; Figure 2 Figure 2 is a structural schematic diagram of the double-layer spinning structure of the composite fiber of the present application from another perspective; Figure 1 Figure 3 is an axial view of the double-layer spinning structure of the composite fiber of the present application; Figure 3 Figure 1 Figure 4 is a structural schematic diagram of the electrospinning nozzle of the present application; Figure 4 Figure 5 is a flowchart of the spinning process of the present application. Figure 5 Figure 5 is a flowchart of the spinning process of the present application.

[0021] ​Explanation of reference numerals: composite fiber body 10, deformation memory outer layer 1, spiral groove 11, spun inner layer 2, dimple 21, electrospinning nozzle 3, inner passage 31, outer passage 32. DETAILED DESCRIPTION

[0022] For the purposes of promoting an understanding of the principles of the application, reference will now be made to the embodiments illustrated in the drawings. It is expressly understood that the drawings are for illustrative purposes and are not a limitation on the scope of the application. In addition, it is to be understood that certain specific features shown in and described with

[0023] It is to be understood that the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise. It is to be understood that the terms "approximately" and "substantially" are used herein to represent the insubstantial difference in the numerical quantity that will not affect the results of the application. It is to be understood that the terms "comprise" and "comprising" are open-ended and are intended to mean that the application can include additional elements or steps.

[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used in the description of the application herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the application. All publications, patent applications, patents, and other references mentioned herein are incorporated by reference in their entirety for the purpose of describing and disclosing, for example, the methodologies and procedures described in such publications, which might be used in connection with the application. Figures 1-5As shown, in an embodiment of the present application, a double-layer spinning structure of composite fiber is involved, including a composite fiber body 10, the composite fiber body 10 including a deformation memory outer layer 1 and a spinning inner layer 2, the deformation memory outer layer 1 being formed of a thermal deformation polyurethane memory material, and the spinning inner layer 2 being a cotton and polyester blended core; the glass transition temperature Tg of the thermal deformation polyurethane memory material is 35±2℃; the cotton accounts for 50-70% and the polyester accounts for 30-50% in the spinning inner layer 2; the deformation memory outer layer 1 and the spinning inner layer 2 are integrally formed by coaxial electrospinning. In this embodiment, the deformation memory outer layer 1 is formed of a thermal deformation polyurethane memory material with a glass transition temperature Tg of 35±2℃, which enables the composite fiber to have a unique temperature response capability. When the ambient temperature reaches or approaches the glass transition temperature, the deformation memory outer layer 1 can undergo reversible deformation. In daily life, for example, when the body temperature of a human body or the external environmental temperature rises to the interval of 33-37℃, the deformation memory outer layer 1 will deform, thereby changing the structural morphology of the composite fiber, possibly increasing the gap between the fibers, improving the air permeability, and making people feel more cool and comfortable; and when the temperature decreases, it can return to the initial state, ensuring the stability of the fiber. The spinning inner layer 2 adopts a cotton and polyester blended core, with the cotton accounting for 50-70% and the polyester accounting for 30-50%. Cotton fibers have good moisture absorption and softness, can absorb sweat excreted by the human body, keep the skin dry, and at the same time give people a comfortable touch; polyester has the advantages of high strength, wear resistance, wrinkle resistance, etc., and the combination of the two makes the spinning inner layer 2 have moisture absorption, comfort and durability. It not only ensures the practicality of the composite fiber in daily use, but also improves its service life and reduces damage caused by friction, washing, etc. The deformation memory outer layer 1 and the spinning inner layer 2 are integrally formed by coaxial electrospinning. The process ensures the close combination of the two-layer structure, making the overall performance of the composite fiber more stable. Integrally forming avoids the problem of separation or delamination between the two layers, ensuring the reliability of the composite fiber in the long-term use process. At the same time, coaxial electrospinning can accurately control the thickness and distribution of the two layers, making the performance of the composite fiber more uniform and consistent, which is conducive to large-scale production and application. This embodiment combines the advantages of various materials, has multiple excellent properties such as temperature response, comfort and durability, etc. through reasonable design and advanced manufacturing process, and has broad application prospects in the fields of textiles, clothing, etc.

[0025] The thermo-deformable polyurethane memory material comprises the following components: shape-memory polyurethane: 80-90 wt%; nano-silica: 5-8 wt%; and an anti-UV agent: 2-5 wt%. The nano-silica has a particle size of 20-40 nm; the anti-UV agent is a benzotriazole. In this embodiment, the shape-memory polyurethane, as the primary component, accounts for 80-90 wt% and imparts the critical thermo-deformable memory function to the composite fiber. Its glass transition temperature (Tg) is 35±2°C. When the ambient temperature approaches or reaches this range, the material undergoes reversible deformation. In practical applications, such as when the human body temperature rises or the ambient temperature changes, the composite fiber can respond to temperature changes. When the temperature rises, the shape-memory outer layer 1 deforms, increasing the inter-fiber spacing and improving breathability, creating a cooler sensation. When the temperature drops, it returns to its original shape, ensuring fiber stability and enhancing the composite fiber's suitability in various temperature environments. The nano-silica has a particle size of 20-40 nm and accounts for 5-8 wt% of the material, enhancing the performance of the composite fiber. Due to its small particle size, large specific surface area and high activity, it can be evenly dispersed in shape memory polyurethane, enhancing the strength and wear resistance of the material. This enables the composite fiber to better resist friction and external forces in daily use, extending the service life of the composite fiber and improving its durability. The anti-ultraviolet agent uses benzotriazole, accounting for 2~5wt%, which effectively improves the anti-ultraviolet ability of the composite fiber. In daily use, composite fibers are inevitably exposed to sunlight, and ultraviolet rays can damage the fiber material, causing material aging and performance degradation. Benzotriazole anti-ultraviolet agents can absorb ultraviolet rays and convert ultraviolet energy into heat energy for release, thereby protecting the shape memory polyurethane and the spinning inner layer 2 material from damage by ultraviolet rays, maintaining the stability of the performance of the composite fiber, and extending its service life in outdoor environments.

[0026] The fiber fineness of the inner layer 2 of the spun yarn is 1.2-1.8D, and the twist is 300-400 TPM; in this embodiment, the fineness range of 1.2-1.8D is moderate in terms of fiber fineness. The finer fiber fineness makes the inner layer 2 of the spun yarn have better softness and smoothness. When in contact with the human body, it can reduce the friction and irritation to the skin, and improve the comfort of wearing. At the same time, the gap between the fine fibers is relatively small, which helps to enhance the barrier ability of the inner layer 2 of the spun yarn to dust and tiny particles in the external environment, and improve the protective performance of the composite fiber. Moreover, fine fibers can increase the specific surface area of the fiber, so that the hygroscopic advantage of cotton fiber can be fully played, and the sweat discharged by the human body can be more effectively absorbed, keeping the skin dry. In terms of twist, the twist of 300-400 TPM ensures that the inner layer 2 of the spun yarn has good strength and stability. The appropriate twist makes the cotton and polyester fibers combine more closely, reducing the possibility of fiber loosening and breaking during use, and improving the durability of the composite fiber. The twist also affects the elasticity and bulkiness of the inner layer 2 of the spun yarn. Within this twist range, the inner layer 2 of the spun yarn has a certain elasticity and can adapt to the activities of the human body without being easily deformed, and also maintains appropriate bulkiness, which helps air circulation inside the fiber, further improving the air permeability of the composite fiber. The appropriate fiber fineness and twist of the inner layer 2 of the spun yarn also have a positive impact on the integrity and stability of the double-layer spun yarn structure of the entire composite fiber. It makes the inner layer 2 of the spun yarn and the shape memory outer layer 1 better combined during the coaxial electrospinning integrated molding process, avoiding the problems of loose combination and delamination between the two layers due to unstable structure of the inner layer 2 of the spun yarn, and ensuring the consistency and reliability of the overall performance of the composite fiber.

[0027] In the above embodiments, tests were carried out under the following table conditions: Material formula:

[0028] Process parameters:

[0029] Fiber structure parameters:

[0030] Test performance includes the following: Temperature response performance:

[0031] Mechanical and durability performance:

[0032] Wearing performance:

[0033] The cross-sectional shape of the composite fiber body 10 is an eccentric circular ring structure, the outer layer thickness ratio of the shape memory outer layer 1 is 30±5%; the diameter of the spinning inner layer 2 is 10-25 μm. In this embodiment, the eccentric circular ring structure makes the composite fiber have differentiated performance in different directions. Compared with the traditional concentric circular ring structure, the eccentric design makes the composite fiber produce more complex deformation response when stressed. When subjected to external force, the fibers on the eccentric side are more prone to bending and deformation, so that the composite fiber as a whole exhibits better flexibility and elasticity. The composite fiber can better adapt to various complex weaving processes during textile processing, and after the finished product is made, it can better fit the human body curve, improve the comfort and fit of wearing. The thickness ratio of the shape memory outer layer 1 is 30±5%, a reasonable thickness ratio can fully exert the characteristics of the thermally induced shape memory polyurethane material, and also ensure that the performance of the spinning inner layer 2 is not affected too much. The appropriate thickness makes the shape memory outer layer 1 quickly and effectively deform when reaching the glass transition temperature, realizing the temperature response function. At the same time, it will not cause the composite fiber to be too hard and heavy as a whole due to the over-thickness of the outer layer, affecting its softness and comfort; nor will it make the thermal induced shape change effect not obvious because of the over-thin outer layer. The diameter of the spinning inner layer 2 is 10-25 μm, which helps to ensure the performance of the spinning inner layer 2 and the combination effect with the outer layer. The appropriate diameter makes the spinning inner layer 2 have good strength and stability, while also ensuring that it has enough contact area with the shape memory outer layer 1, so that it can realize close combination and form a stable double-layer structure during the coaxial electrospinning integrated molding process. Moreover, the spinning inner layer 2 with this diameter range can better exert the advantages of cotton and polyester blending, balancing the properties of moisture absorption, comfort and durability, etc.

[0034] The outer surface of the spinning inner layer 2 is provided with pits 21, and the shape memory outer layer 1 fills the pits 21 through coaxial electrospinning to form a microporous interlocking structure, the depth size of the pits 21 is 2-5 μm, and the diameter is 1-3 μm; in this embodiment, the microporous interlocking structure greatly enhances the bonding force between the spinning inner layer 2 and the shape memory outer layer 1. The pits 21 are like anchor points, so that the shape memory outer layer 1 is closely connected with the spinning inner layer 2 after filling, and when the fiber is subjected to external force pulling, friction or bending, etc., the relative sliding or separation between the two layers is not easy to occur, which ensures the integrity and stability of the overall structure of the composite fiber, effectively improves the durability and service life of the fiber. The microporous interlocking structure creates more contact area, promotes the material transfer and interaction between the two layers. For example, the hygroscopicity of cotton fibers in the spinning inner layer 2 can be better transferred to the shape memory outer layer 1 through the microporous structure, so that the overall moisture-wicking performance of the composite fiber is optimized. At the same time, the performance of nano-silicon dioxide and other ingredients in the shape memory outer layer 1 can also more effectively affect the spinning inner layer 2, enhancing the comprehensive performance of the composite fiber, such as strength, wear resistance, etc. The microporous structure itself has certain adsorption and air permeability. The micropores formed by the pits 21 can adsorb small particles, odor molecules and other substances in the surrounding environment, and have a certain purification effect. Moreover, these micropores provide channels for the circulation of air, which helps to improve the air permeability of the composite fiber, so that the wearer can maintain dryness and comfort during use, especially suitable for the field of textiles with high comfort requirements.

[0035] The outer surface of the deformation memory outer layer 1 is provided with a spiral groove 11, the groove depth size of the spiral groove 11 is 0.5-1.2 μm, the pitch is 15-30 μm; the surface area ratio of the spiral groove 11 is ≥40. In this embodiment, the spiral groove 11 increases the specific surface area of the deformation memory outer layer 1. The surface area ratio ≥40 makes the contact area of the composite fiber with the external environment significantly increase. For the effect of the anti-ultraviolet agent, a larger surface area means that more anti-ultraviolet agents can contact with ultraviolet rays, thereby more efficiently absorbing and scattering ultraviolet rays, greatly enhancing the anti-ultraviolet ability of the composite fiber, effectively protecting the spinning inner layer 2 and the entire composite fiber structure from ultraviolet damage, and prolonging the service life of the composite fiber. From the functional point of view, the spiral groove 11 plays a good moisture guiding role. When there is moisture on the surface of the composite fiber, the spiral structure can guide the moisture to flow along the groove direction, accelerate the evaporation speed of the moisture, and improve the moisture absorption and sweat releasing performance of the composite fiber. In actual application, such as when making sports clothes, it can keep the human body dry and improve the comfort of wearing. In terms of structural stability, the spiral groove 11 provides a certain buffering and anti-deformation ability for the composite fiber. The design of the groove depth size of 0.5-1.2 μm and the pitch of 15-30 μm makes the composite fiber disperse stress when subjected to external force, avoiding fiber damage caused by local stress concentration. When the fiber is stretched, bent or extruded, the spiral structure can absorb and release energy through its own deformation to ensure the integrity of the overall structure of the composite fiber. In this embodiment, the existence of the spiral groove 11 also enhances the surface friction of the composite fiber. It is of great significance in some application scenarios that require anti-skid performance, such as when making gloves, socks and other products, it can improve the friction between the product and the contacted object, enhance the convenience and safety of use.

[0036] The preparation process of the composite fiber body 10 includes: spinning the polyurethane solution through the electrospinning nozzle 3, which is a coaxial double-channel structure. The electrospinning nozzle 3 includes an inner channel 31 for hot melt spinning of the cotton and polyester blended core, and an outer channel 32 for electrospinning of the polyurethane solution with a concentration of 18-22 wt% at a voltage of 25-35 kV. The polyurethane solution is electrospun to coat the inner layer 2 to form the deformation memory outer layer 1. In this embodiment, from the preparation of the inner layer 2, the inner channel 31 hot melt spins the cotton and polyester blended core and extrudes at a cooling temperature of 60-80°C. This can fully fuse the cotton fibers and polyester fibers and take advantage of both. Cotton fibers have good moisture absorption and comfort, keeping the skin dry; polyester fibers provide high strength and wear resistance. A suitable cooling temperature helps to control the crystallinity and orientation of the fibers, ensuring that the inner layer 2 has stable physical properties and structure, so that it is not easily deformed and damaged in subsequent use. The outer channel 32 uses a polyurethane solution with a concentration of 18-22 wt% for electrospinning at a voltage of 25-35 kV to coat the inner layer 2. The polyurethane solution with the appropriate concentration ensures the spinnability of the solution and the quality of the formed fibers. Precise control of the voltage allows the polyurethane solution to be uniformly and stably sprayed and coated on the inner layer 2, forming a deformation memory outer layer 1 with uniform thickness and consistent performance. From the combination of the double-layer structure, the coaxial double-channel electrospinning process realizes the close combination of the inner layer 2 and the deformation memory outer layer 1. Under the action of static electricity, the deformation memory outer layer 1 can well fit the inner layer 2, forming a stable double-layer structure. Moreover, this combination makes the interface between the two layers transition naturally, which is beneficial to the transmission and dispersion of stress, improving the strength and flexibility of the composite fiber as a whole. The polyurethane material of the deformation memory outer layer 1 has temperature response characteristics and can deform according to the change of external temperature, while the performance of the inner layer 2 ensures the basic use performance of the composite fiber. The combination of the two makes the composite fiber maintain good performance in different environmental conditions, and has a wide application prospect, such as being used in intelligent textiles, functional clothing and other fields.

[0037] The composite fiber body 10 exhibits temperature-responsive deformation properties: when the temperature exceeds Tg, the outer layer shrinks by 15% or more; when the temperature is below Tg, the deformation recovery rate is 98% or more. In this embodiment, from a functional perspective, the temperature-responsive property enables the composite fiber to achieve intelligent adjustment capabilities. When the temperature exceeds Tg, the outer layer shrinks by 15% or more. In practical applications, such as in the production of intelligent temperature-regulating clothing, when the external temperature rises, the outer layer of the composite fiber shrinks, increasing the porosity of the fabric and enhancing air circulation, accelerating the dissipation of body heat, thereby keeping the wearer cool. It can also be applied to industrial products that require shape or performance changes based on temperature, enabling active response and adjustment to temperature changes. When the temperature is below Tg, the deformation recovery rate is 98% or more. This high recovery rate ensures the composite fiber's reusability and structural stability. After experiencing deformation caused by temperature changes, the composite fiber can almost completely recover to its original state. This ensures that the product's performance will not significantly degrade due to repeated temperature cycles during long-term use. In the field of textiles, clothing can still maintain its original shape and performance after multiple washes and changes in temperature environments, extending the service life of the product. From the perspective of the synergy of the double-layer spinning structure, the temperature-responsive deformation characteristics promote the good coordination between the spinning inner layer 2 and the shape memory outer layer 1. The contraction and recovery of the outer layer will produce a certain stress on the spinning inner layer 2. The stress makes the bond between the two layers tighter, further enhancing the overall structural stability of the composite fiber. At the same time, during the temperature change process, the interaction between the two layers can also produce some additional performance improvements, such as improving the elasticity and flexibility of the composite fiber.

[0038] The composite fiber body 10 is used for temperature adjustment fabric, the weaving density of the composite fiber body 10 is 80~120 root / cm², when the ambient temperature is >35℃, the composite fiber body 10 changes the weaving density under the action of the deformation memory outer layer 1.The embodiment in temperature regulation, when the ambient temperature is >35℃, the composite fiber body 10 changes the weaving density under the action of the deformation memory outer layer 1.Because the weaving density of the composite fiber body 10 is originally 80~120 root / cm², when the temperature rises, the deformation memory outer layer 1 responds, and the weaving of the composite fiber body 10 becomes loose.This change increases the porosity of the fabric, allowing air to flow more freely in the fabric.The flow of air speeds up the heat exchange between the human body and the external environment, can quickly take away the heat generated by the human body, reduces the temperature of the human body surface, makes the wearer keep cool and comfortable in the high temperature environment, realizes the active temperature adjustment function of the fabric.From the structural stability point of view, the double-layer spinning structure provides a stable basis for the weaving density change of this temperature responsiveness.The spinning inner layer 2 and the deformation memory outer layer 1 are closely combined through microporous interlocking structure and the like, to ensure that the two layers will not separate during the deformation process.Even in the process of weaving density change caused by multiple temperature changes, the composite fiber can still maintain its integrity and stability, ensuring the performance reliability of the fabric in long-term use.In the wearing experience, the appropriate initial weaving density of the composite fiber body 10 makes the fabric have good texture and comfort.In normal temperature, the weaving density of 80~120 root / cm² makes the fabric have a certain tightness, and will not be too heavy.When the weaving density changes when the temperature rises, the comfort of wearing is further optimized, and the wearer will not feel stuffy or restricted because of high temperature.

[0039] Referring to Figures 1-5 As shown in the figure, a spinning process for preparing the double-layer spinning structure of the composite fiber includes the following steps: Step S1, core blending pretreatment: cotton and polyester are mixed in a ratio of 50~70%:30~50%, and a spinning inner layer 2 with a fiber fineness of 1.2~1.8D and a twist of 300~400TPM is formed by melt spinning; Step S2, polyurethane solution preparation: shape memory polyurethane 80-90wt%, nano silicon dioxide 5~8wt%, and benzotriazole ultraviolet resistant agent 2~5wt% are dissolved in DMF solvent to prepare a spinning solution with a concentration of 18~22wt%; Step S3, coaxial electrospinning: the spinning core layer is extruded through the inner channel 31, and the cooling roller temperature is 60~80℃; the polyurethane solution is extruded through the outer channel 32, and a static voltage of 25~35kV is applied to coat the core layer; Step S4, microporous interlocking forming: the polyurethane solution is filled into the surface pit 21 of the core layer to form a microporous interlocking structure.

[0040] In this embodiment, in the blended core pretreatment step, cotton and polyester are mixed in a specific ratio to form a specific fiber fineness and twist of the inner layer 2 of the spun yarn. The reasonable ratio of cotton and polyester not only plays the hygroscopicity and soft touch of cotton, but also combines the high strength and wear resistance of polyester, so that the inner layer 2 of the spun yarn has good comprehensive performance. The appropriate fiber fineness and twist can ensure the uniformity and stability of the inner layer 2 of the spun yarn, lay the foundation for the overall performance of the subsequent composite fiber, and avoid structural defects caused by uneven fiber thickness or improper twist. In the polyurethane solution preparation step, the shape memory polyurethane, nano silicon dioxide and benzotriazole ultraviolet resistant agent are dissolved in DMF solvent in a certain proportion to prepare the spinning solution. The shape memory polyurethane gives the composite fiber the function of thermal deformation memory, and its glass transition temperature can make the fiber reversibly deform according to the change of environmental temperature. The addition of nano silicon dioxide enhances the strength and wear resistance of the fiber, and improves the service life of the composite fiber. The benzotriazole ultraviolet resistant agent can effectively absorb ultraviolet rays, protect the fiber from ultraviolet damage, and prolong the use time of the fiber in outdoor environment. The coaxial electrospinning step uses the inner channel 31 to extrude the core layer of the spun yarn and is shaped by the cooling roller, and the outer channel 32 extrudes the polyurethane solution and applies an electrostatic voltage to coat the core layer. It ensures that the two-layer structure is tightly combined, the temperature control of the cooling roller ensures the forming quality of the core layer of the spun yarn, and the application of the electrostatic voltage makes the polyurethane solution uniformly coat the core layer, forming a complete and stable double-layer structure. The microporous interlocking forming step controls the polyurethane solution to fill the surface pits 21 of the core layer, forming a microporous interlocking structure. It enhances the bonding force between the two layers, makes the overall performance of the composite fiber more stable, and improves the mechanical properties and stability of the composite fiber. At the same time, the microporous structure may give the composite fiber some special properties, such as air permeability and adsorbability, etc. Through the synergistic effect of each step in this embodiment, the composite fiber double-layer spun yarn structure prepared has excellent comprehensive performance, good practicality and application prospect.

[0041] In step S2, the spinning solution is subjected to maturation treatment: maturation temperature: 40±2℃; maturation time: 12-24h; viscosity after maturation: 4500±500mPa·s. From the perspective of molecular structure, under the conditions of a maturation temperature of 40±2℃ and a maturation time of 12-24h, the polymer chains in the spinning solution can move and rearrange sufficiently. This allows the formation of more ordered and stable structures between polymer chains, which helps to enhance the cohesion and uniformity of the spinning solution. The viscosity of 4500±500mPa·s after maturation provides ideal fluidity and formability for the spinning process. Suitable viscosity can ensure that the spinning solution maintains a stable flow state during the extrusion process, avoiding problems such as droplet splashing or filament breakage, thereby improving the continuity and stability of the spinning process. In terms of fiber performance, the fibers prepared from the spinning solution subjected to such maturation treatment have better physical properties. Due to the more ordered arrangement of molecular chains, the strength and toughness of the fibers are significantly improved. In practical applications, they can withstand greater tensile force and external force without easily breaking, improving the durability and service life of fiber products. At the same time, the uniformity of the fibers is also improved, making the thickness of the fibers more consistent and the appearance quality better. This is of great significance for some application fields with high requirements for fiber quality, such as high-end textiles and high-performance composites. Precise control of the maturation conditions makes the spinning process more stable and repeatable. The viscosity of the spinning solution after each maturation can be maintained within the range of 4500±500mPa·s, which means that the parameters of the spinning process can remain relatively consistent in different batches of spinning production, reducing the differences in product quality caused by fluctuations in the properties of the spinning solution. This helps to improve production efficiency, reduce production costs, and ensure the stability and consistency of product quality.

[0042] Also included is the forming of helical grooves 11: when the fiber is not fully cured, at a curing degree of 60-70%, the helical grooves 11 are formed by impressing with a textured roller. In this embodiment, from the perspective of the performance of the fiber, the formation of the helical grooves 11 greatly increases the specific surface area of the fiber. The larger specific surface area increases the contact area of the fiber with the surrounding medium, and in some application scenarios, such as in the field of adsorbent materials, it can improve the adsorption capacity of the fiber for target substances in gases or liquids. For filter materials, it can also enhance the interception and filtration effect of impurities, and improve the filtration efficiency and precision. From the functional aspect of the fiber, the helical grooves 11 endow the fiber with special optical and acoustic properties. Due to the presence of the helical grooves 11, the way light is reflected and refracted on the surface of the fiber becomes more complex, and special optical effects such as color change or light reflection effects can be produced, which have potential application value in some decorative textiles or anti-counterfeiting materials. At the same time, the spiral structure can also change the propagation characteristics of sound in the fiber, so that the fiber has certain sound absorption or sound insulation function, and can be used for the preparation of acoustic materials. The helical groove 11 forming is selected to be performed when the fiber curing degree is 60-70%. At this time, the fiber has a certain plasticity and can form clear and stable helical grooves 11 by impressing with a textured roller, and it will not deform or fail to form due to being too soft. Precise process control ensures the quality and consistency of the helical grooves 11, so that each fiber has similar performance and appearance, which is conducive to large-scale production and application.

[0043] The above embodiments only express several embodiments of the present application, and the description is more specific and detailed, but it cannot be understood as limiting the scope of the patent of the present application. It should be noted that for ordinary skilled persons in the art, without departing from the concept of the present application, several modifications and improvements can be made, which are within the scope of protection of the present application. Therefore, the protection scope of the patent of the present application should be subject to the appended claims.

Claims

1. A double-layer spinning structure of a composite fiber, characterized by: It includes a composite fiber body, which includes a shape memory outer layer and a spinning inner layer. The shape memory outer layer is formed of a thermo-deformable polyurethane memory material, and the spinning inner layer is a cotton and polyester blended core; the glass transition temperature Tg of the thermo-deformable polyurethane memory material is 35±2°C; the cotton proportion of the spinning inner layer is 50~70%, and the polyester proportion is 30~50%; the shape memory outer layer and the spinning inner layer are integrally formed by coaxial electrospinning.

2. The double-layer spinning structure of the composite fiber according to claim 1, characterized in that: The thermo-deformable polyurethane memory material comprises the following components: Shape memory polyurethane: 80~90wt%; Nano-silicon dioxide: 5~8wt%; Anti-ultraviolet agent: 2~5wt%; The particle size of the nano-silicon dioxide is 20-40 nm; The UV inhibitor is benzotriazole.

3. The double-layer spinning structure of the composite fiber according to claim 1, characterized in that: The fiber fineness of the spinning inner layer is 1.2~1.8D, and the twist is 300~400TPM; The cross-sectional shape of the composite fiber body is an eccentric circular ring structure, the outer layer thickness of the deformation memory outer layer accounts for 30±5%; and the diameter of the spinning inner layer is 10~25μm.

4. The double-layer spinning structure of the composite fiber according to claim 1, characterized in that: The outer surface of the spinning inner layer is provided with pits, and the shape memory outer layer is filled with the pits by coaxial electrospinning to form a microporous interlocking structure, and the depth of the pits is 2-5 μm and the diameter is 1-3 μm; The outer surface of the shape memory outer layer is provided with a spiral groove, the groove depth of the spiral groove is 0.5-1.2 μm, and the pitch is 15-30 μm; the surface area ratio of the spiral groove is ≥40.

5. The double-layer spinning structure of the composite fiber according to claim 1, characterized in that: The preparation process of the composite fiber body includes: The polyurethane solution is spun by an electrospinning nozzle, which has a coaxial dual-channel structure: the electrospinning nozzle includes an inner channel and an outer channel, the inner channel is used for hot-melt spinning of a cotton and polyester blended core, and extruded to form a spinning inner layer after cooling to a temperature of 60-80°C; the outer channel is used for electrospinning a polyurethane solution with a concentration of 18-22wt% at a voltage of 25-35kV, and the polyurethane solution is spun by the electrospinning nozzle and coated on the spinning inner layer to form a deformation memory outer layer.

6. The double-layer spinning structure of the composite fiber according to claim 1, characterized in that: The composite fiber body has a temperature-responsive deformation characteristic: when the temperature is greater than Tg, the outer layer shrinkage rate is greater than or equal to 15%; when the temperature is less than Tg, the deformation recovery rate is greater than or equal to 98%.

7. The double-layer spinning structure of the composite fiber according to claim 1, characterized in that: The composite fiber body is used for temperature-regulating fabrics. The weaving density of the composite fiber body is 80 to 120 fibers / cm². When the ambient temperature is greater than 35°C, the composite fiber body changes its weaving density under the action of the shape-memory outer layer.

8. A spinning process for preparing a double-layer spinning structure of the composite fiber according to any one of claims 1 to 7, characterized in that: The steps include: Step S1, pretreatment of the blended core: cotton and polyester are mixed in a ratio of 50-70%: 30-50%, and melt-spun to form a spinning inner layer with a fiber fineness of 1.2-1.8D and a twist of 300-400 TPM; Step S2, preparing a polyurethane solution: dissolving 80-90 wt% of shape memory polyurethane, 5-8 wt% of nano-silica, and 2-5 wt% of a benzotriazole anti-ultraviolet agent in DMF solvent to prepare a spinning solution with a concentration of 18-22 wt%; Step S3, coaxial electrospinning: the spinning core layer is extruded through the inner channel and the cooling roller temperature is set at 60-80°C; the polyurethane solution is extruded through the outer channel and an electrostatic voltage of 25-35 kV is applied to coat the core layer; Step S4, microporous interlocking molding: controlling the polyurethane solution to fill the pits on the surface of the core layer to form a microporous interlocking structure.

9. The spinning process according to claim 8, characterized in that: In step S2, the spinning solution is subjected to aging treatment: aging temperature: 40±2°C; aging time: 12-24 hours; viscosity after aging: 4500±500 mPa·s.

10. The spinning process according to claim 8, characterized in that: It also includes spiral groove forming: when the fiber is not fully cured, at a curing degree of 60-70%, a spiral groove is formed by embossing with an engraved roller.

Citation Information

Cited By

  • Intelligent bionic wound management system and preparation method thereof

    CN122182282A